1977
DOI: 10.1126/science.836589
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Binding: A Difference Between Human and Bovine Milk

Abstract: Gel chromatography indicated that most of the zinc in cow's milk was associated with high-molecular-weight fractions, whereas zinc in human milk was associated with low-molecular-weight fractions. A species difference in zinc-binding ligands may explain why symptoms of the genetic disorder of zinc metabolism, acrodermatitis enteropathica, can be alleviated by feeding human but not cow's milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

1977
1977
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(26 citation statements)
references
References 12 publications
2
22
0
2
Order By: Relevance
“…The results presented here demonstrate that rat milk contained a ZBL similar in size to that found previously by us in human milk (1) and validate the use of the rat as a model to test the hypothesis that this ZBL may be involved in absorption of zinc in the neonate. A ZBL similar to that found in rat milk was identified in the rat intestine of 16-to 28-day-old animals but was absent in younger animals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results presented here demonstrate that rat milk contained a ZBL similar in size to that found previously by us in human milk (1) and validate the use of the rat as a model to test the hypothesis that this ZBL may be involved in absorption of zinc in the neonate. A ZBL similar to that found in rat milk was identified in the rat intestine of 16-to 28-day-old animals but was absent in younger animals.…”
Section: Discussionsupporting
confidence: 87%
“…Van Campen and Kowalski (12) have reported the presence of compounds of low molecular weight (10,(0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)000) Proc. Nati.…”
Section: Discussionmentioning
confidence: 99%
“…The non-citrate bound zinc is also distributed similarly in the milk of the two species, but very different from most other species studied (16). As seen with iron absorption from human milk, it has been suggested that the high bioavailability of zinc from human milk relative to cow's milk may be due to a difference in molecular localization of zinc in the milks (9,24). The monkey thus presents a model in which this hypothesis may be tested.…”
Section: Methodsmentioning
confidence: 99%
“…The nonexchangeable space represents Ca2+ sequestered in su~cellular storage granules, and alteration of Ca" binding and/or.fluxes in the other compartments has an important role in the process of platelet aggregation and exocytosis (I). In subjects with Down's syndrome, blood platelets have decreased Na+/Kt-ATPase activity and increased intracellular Na+ (9). In erythrocytes, it has been reported that Na+/K+-ATPase is inhibited by increases in intracellular Ca2+ (2, 3), which may lead to raised intracellular Na+ (1 3); thus, it seemed pertinent to determine the Ca2+ content of blood platelets from subjects with Down's syndrome as a possible factor contributing to decreased Na+/K+-ATPase activity.…”
mentioning
confidence: 99%
“…The chemical composition of human milk exhibits considerable variation between different individuals and in the same individual at different times of lactation (15), as well as between samples obtained from mothers of LBW infants and full term infants (16,17 (20). In addition, a zinc binding ligand, which promotes absorption of zinc, has been identified & the human milk (21,22): Human milk is considered to be deficient in vitamin D (9). Temporal studies of human milk have indicated that the concentration of many chemical components, especially nitrogen, calcium, and sodium decrease significantly as the duration of lactation increases (9, 10); however, several components have been found to change in concentration as a function of water content, because their total daily output appears to be remarkably constant at least during the first 8 wk of lactation (23,24).…”
Section: Composition Of Human Milkmentioning
confidence: 99%